Penilaian Praktik Penanganan Limbah Pada Kapal Yang Beroperasi di Wilayah Pesisir Nusa Tenggara Timur - Nugraha, I Made Aditya (Universitas Mataram, 2025)
Marine environmental pollution due to shipping activities is a strategic issue in coastal area management. To address this, the Indonesian Government issued Regulation of the Minister of Transportation Number 29 of 2014 as a guideline for preventing pollution from ships. This study aims to evaluate ship waste management practices in the coastal area of East Nusa Tenggara, especially on passenger ships that operate regularly, and to assess the implementation of these regulations. The methods used include direct observation, interviews with ship crews, and literature studies on national regulations and international conventions such as MARPOL 73/78. The results of the study indicate that ships have implemented waste management according to standards, both for solid waste (organic and inorganic) from the deck area and liquid waste (oil and sludge) from the engine room. The management stages include collection, storage, unloading, and transportation to facilities on land. The ship also has a pollution prevention certificate as stipulated in Article 57 of Regulation of the Minister of Transportation 29 of 2014. This implementation shows compliance with regulations and increased awareness of ship crews towards preserving the marine environment. These findings can be a reference for ship waste management practices that support sustainable maritime development.